Leveraging Emerging Technologies and Analytics for Empowering Humanity, Vol. 1 International Conference Proceedings of LEAD-2024, IIM Shillong, December 10–12 - Goyal, D P.; Sarker, Suprateek; Mukhopadhyay, Somnath; Roychoudhury, Basav; Upadhyay, Parijat; Dadabada, Pradeep Kumar (Springer Proceedings in Business and Economics, 2025)
XII, 460 p. 104 illus., 83 illus. in color.